2000
DOI: 10.1042/0300-5127:0280969
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic oil palm: production and projection

Abstract: Oil palm is an important economic crop for Malaysia. Genetic engineering could be applied to produce transgenic oil palms with high value-added fatty acids and novel products to ensure the sustainability of the palm oil industry. Establishment of a reliable transformation and regeneration system is essential for genetic engineering. Biolistic was initially chosen as the method for oil palm transformation as it has been the most successful method for monocotyledons to date. Optimization of physical and biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…As a consequence of the biological characteristics of oil palm (long life cycle and no natural vegetative reproduction) and a high heterogeneity prevalent among hybrids, breeding strategies are labor intensive and time consuming [5,6]. Moreover, planting materials at present are derived from a narrow gene pool, which provides breeders with limited genetic variability for improvement [3]. Therefore, the palm oil industry has invested in the development of new techniques for multiplying agronomically interesting and superior parents, primarily of high oil and fruit yielding characteristics, for seed production and elite progeny palms for commercial planting [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of the biological characteristics of oil palm (long life cycle and no natural vegetative reproduction) and a high heterogeneity prevalent among hybrids, breeding strategies are labor intensive and time consuming [5,6]. Moreover, planting materials at present are derived from a narrow gene pool, which provides breeders with limited genetic variability for improvement [3]. Therefore, the palm oil industry has invested in the development of new techniques for multiplying agronomically interesting and superior parents, primarily of high oil and fruit yielding characteristics, for seed production and elite progeny palms for commercial planting [7].…”
Section: Introductionmentioning
confidence: 99%
“…my/economy/EID_web.htm). The challenge that the oil palm industry will face in the 21st century is its ability to maintain competitiveness and remain profitable while facing labor shortages and limited land resources [3]. In addition, the demand for palm oil is expected to increase in the future as the world population increases.…”
Section: Introductionmentioning
confidence: 99%
“…Oil palm transformation studies also revealed that ubiquitin promoter is an efficient and stable promoter in oil palm transformed tissues Parveez et al 1997). In addition, production of transgenics oil palm carrying the bar gene driven by ubiquitin promoter, which are resistant to herbicide Basta TM have been successful obtained (Parveez et al 2000). In order to control expression of transgenes in oil palm mesocarp, the MSP1 promoter (1140 bp) has been used to drive expression of the GOI.…”
Section: Results and Discussion Phs41mentioning
confidence: 99%
“…(2000) for the particle bombardment mediated genetic engineering of oil palm can be used to accelerate the genetic transformation of oil palm with constructs reported in this study to knockout the PATE gene expression [07]. Recently, constitutive and oil palm leaf-specific promoters (and their potential applications) has been reported by Masura et al .…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this goal, conventional crop improvement methods are not only tedious but also time-consuming [5]. Oil palm genetic engineering may save 80-90% of the time required for insertion of gene/s for new trait/s in it through conventional crop breeding [7]. Therefore, out of all existing methods available for crop improvement, perhaps genetic engineering is the best method to manipulate fatty acid profile in oil palm in a short period.…”
Section: Introductionmentioning
confidence: 99%